2012
DOI: 10.1029/2011jd017141
|View full text |Cite
|
Sign up to set email alerts
|

Estimating surface longwave radiative fluxes from satellites utilizing artificial neural networks

Abstract: [1] A novel approach for calculating downwelling surface longwave (DSLW) radiation under all sky conditions is presented. The DSLW model (hereafter, DSLW/UMD v2) similarly to its predecessor, DSLW/UMD v1, is driven with a combination of Moderate Resolution Imaging Spectroradiometer (MODIS) level-3 cloud parameters and information from the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-Interim model. To compute the clear sky component of DSLW a two layer feed-forward artificial neural network wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Earlier estimates of E l↓ were based on surface measurements of air temperature and humidity and observations of cloud cover (Brunt, ) justified by the fact that the greater part of the down‐welling long‐wave flux is emitted from the near surface layers of the atmosphere (Elsasser, , Nussbaumer and Pinker, ). Recent studies have confirmed that surface measurements of air temperature and humidity when combined as specific humidity provide an accurate proxy for measurements of E l↓ under all sky conditions and over a wide range of climates.…”
Section: Introductionmentioning
confidence: 94%
“…Earlier estimates of E l↓ were based on surface measurements of air temperature and humidity and observations of cloud cover (Brunt, ) justified by the fact that the greater part of the down‐welling long‐wave flux is emitted from the near surface layers of the atmosphere (Elsasser, , Nussbaumer and Pinker, ). Recent studies have confirmed that surface measurements of air temperature and humidity when combined as specific humidity provide an accurate proxy for measurements of E l↓ under all sky conditions and over a wide range of climates.…”
Section: Introductionmentioning
confidence: 94%
“…The fluxes are derived globally and gridded to 0.5° at 3 hourly time scale from July 1983 to December 2009; they include both SW↓ [ Ma and Pinker , ] and LW↓ [ Nussbaumer and Pinker , ] flux components. For the period from January 2002 to December 2012, using an inference scheme labeled as UMD_MODIS_SW for SW↓ [ Wang and Pinker , ] and UMD_MODIS_LW for LW↓ [ Nussbaumer and Pinker , ], they are implemented globally with products from the Moderate Resolution Imaging Spectroradiometer (MODIS) sensor both on Aqua and Terra [ King et al ., ] at 1° spatial resolution at daily time scale (additional details on the ISCCP DX‐based data are presented in Appendix ). Methodology how to homogenize the satellite estimates from the two independent sources, namely, ISCCP DX and Modis, is described in Appendix . ERA‐Interim (ERA‐I) [ Berrisford et al ., ; Dee et al ., ] data as downloaded from http://rda.ucar.edu.…”
Section: Data To Be Usedmentioning
confidence: 99%
“…Methodologies to derive radiative fluxes from long‐term satellite observations are described, for example, in Zhang et al . [] and Ma and Pinker [], methods that use more recent satellite observations (as also used in this study) are described in Wang and Pinker [] and Nussbaumer and Pinker []. The methodologies how the various fluxes were computed will be summarized in section 2.…”
Section: Introductionmentioning
confidence: 99%